A replication study of a psychotherapy incorporating horses resiliency intervention for healthcare workers - William R. Marchand; Laurie Sullivan-Sakaeda; Ryan Lackner; Dylan Taplin; Elena Nazarenko (Elsevier, 2023)
Objectives: The first aim of this pilot observational study was to replicate a previous study of a resiliency psychotherapy incorporating horses (PIH) intervention for healthcare workers. The second aim was to address some gaps in the literature regarding equine-assisted services more broadly. Design: Prospective open trial. Setting: A large healthcare system and a community equine facility Intervention: A single-session four-hour intervention that focused on participants resilience. Main outcome measures: Safety, feasibility, and utilization were assessed, and psychological instruments were administered. Instruments utilized were the Positive and Negative Affect Scale the Acceptance and Action Questionnaire II, and the Conner-Davidson Resiliency Scale. Results: Thirty-eight subjects participated in the study, the majority of which were female (71.1 %). The age group with the most representation included those ranging from age 25-34. The intervention was safe but underutilized. Participation was associated with improved psychological flexibility (PF), and positive affect, as well as reduction in negative affect pre- to post-intervention. There was no change in resiliency and there were no associations between improvements in affect and PF. Conclusions: Resiliency PIH interventions for healthcare workers can be utilized safely and likely result in short-term psychological benefits for participants. Future randomized controlled investigations are warranted, and these studies should implement methods to maximize utilization. Additionally, this study and the literature suggest that enhanced affect and PF are likely important EAS outcomes across a variety of interventions. These constructs should be investigated with more rigorous studies including comparisons of interventions with and without a psychotherapy component.